Interleukin-31: A Pro-inflammatory Oriented Cytokine - Giuseppe Murdaca; Francesca Paladin; Andrea Orsi; Sebastiano Gangemi (Frontiers in Bioscience-Landmark)
Type 2 immunity is represented by T helper 2 (Th2) lymphocytes and the cytokines produced downstream (Interleukin (IL)-4, IL-13, IL-31). They are increasingly recognized as pivotal mediators in the pathogenesis of immune-mediated dermatological conditions such as atopic dermatitis (AD) and psoriasis (Pso). In these disorders, they initiate and amplify immunological signaling cascades, promote cutaneous inflammation, and contribute to the induction of pruritus. In this context, IL-33 and IL-31 would be believed to be intrinsically linked and related to the acuity of the disease. The presence of an interleukin could in fact trigger the other, amplifying the inflammatory process of itchy skin disorders and therefore the extent of the symptoms. High levels of IL-31 may support the maintenance of a microenvironment that promotes both the growth and spread of solid tumors, as well as the development of cancer-associated pruritus. Given these premises, non-histaminergic mediators such as IL-31 and IL-33 could be explored as novel therapeutic targets for the treatment of pruritus in immune-mediated skin diseases and cancer, improving the QoL of patients. Finally, we briefly discussed the recent innovations in the field of monoclonal anti-IL-31 therapies.